Digital government, circular economy, and public value creation: orga-nizational factors in the adoption of digital technologies in the Federal District (Brazil) and New York State (United States) - Júlio Cezar Costa Ramos; Eduardo Augusto Rodrigues Barros; Luiz Henrique Paiva Pires (OBSERVATÓRIO DE LA ECONOMÍA LATINOAMERICANA, 2026)
Digital government initiatives are increasingly mobilized to address complex, cross-boundary policy challenges, yet their contribution to public value creation remains highly contingent on organizational and institutional conditions. This paper examines how organizational capacity and interorganizational coordination shape the adoption and use of digital government initiatives in circular economy governance. Building on public value theory and governance network perspectives, the study adopts a qualitative comparative institutional design, analyzing the Federal District (Brazil) as the primary empirical case and drawing analytical insights from New York State (United States). Empirical evidence is based on semi-structured interviews with public managers and technical staff, complemented by document analysis and institutional observation conducted during a visiting PhD period at a U.S. public policy school. The findings show that digital technologies contribute to transparency and information integration, but their capacity to generate public value—such as policy coherence, effectiveness, and sustainability—is fundamentally mediated by organizational capacity, coordination mechanisms, and institutional stability. By explicitly linking circular economy governance to organizational and networked perspectives on public value creation, the study advances digital government research and offers implications for governments in both developing and developed contexts. This is not a comparison between the global North and South, but rather a qualitative study seeking to improve concepts of digital government in both Brazil and the United States.